Acute generalized exanthematous pustulosis due to ceftriaxone: Report of a pediatric case with recurrence after positive patch test - SALMAN, ANDAÇ; KEPENEKLİ KADAYİFCİ, EDA (WILEY, 2019)
Acute generalized exanthematous pustulosis (AGEP) is seen uncommonly in children and sometimes shows atypical clinical features in this population. Patch testing can be used effectively in children for the confirmation of the culprit drug in cases of multiple drug use. Here, we report a rare, pediatric case of ceftriaxone-induced AGEP confirmed by patch testing with subsequent recurrence of the skin eruption.
Keywords: acute generalized exanthematous pustulosis; allergy; ceftriaxone; drug reaction; patch testing; UNCOMMON CONDITION; AGEP